Hypersensitivity reactions to iodinated contrast media: potential mechanisms and clinical management - Zhong, Xia; Zhao, Lihong (Frontiers in Medicine, 2025)
Iodinated contrast media (ICM) are indispensable in modern imaging, but hypersensitivity reactions (HSRs), ranging from mild urticaria to severe anaphylaxis, remain a significant and evolving clinical challenge. Although advancements in ICM formulations and HSR management, ongoing discussions and uncertainties persist, particularly regarding variable epidemiology, complex mechanisms, and debatable clinical management strategies. This review provides a comprehensive overview and insights into the epidemiology, clinical consequences, potential mechanisms, clinical management, and current controversies associated with HSRs to ICM. Ongoing research is critical, focusing on areas such as monitoring epidemiological trends, uncovering underlying mechanisms, improving risk prediction, and refining preventive, diagnostic, and therapeutic strategies. Overall, as the use of ICM continues to rise, balancing their diagnostic benefits with effective management of HSRs is essential to optimizing patient safety and clinical outcomes.